Predisposisi Tuberkulosis Paru: A Cross Sectional Study - Erni Yetti R; Zadrak Tombeg; Anto J. Hadi (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2021)
Pulmonary tuberculosis is a contagious disease and can affect various age groups and is experienced by many people with middle to lower-income. This study aimed to determine the factors associated with pulmonary tuberculosis incidence. Analytical observational research with a cross-sectional study approach at Puskesmas Makale Utara, Tana Toraja Regency, was conducted for two weeks and conducted in October 2020. In this study, the population and sample were patients visited in one period at the Puskesmas through the accidental sampling method. Collecting data using a research questionnaire and data analysis using Chi-Square. The results showed that knowledge (p = 0.001), type of work (p = 0.001), smoking habits (p = 0.000) were associated with pulmonary tuberculosis. The conclusion is that knowledge, type of work, and smoking habits predispose pulmonary tuberculosis incidence factors. So that patients can adopt a healthy lifestyle and consume nutritious foods.